Death in paradise. Season six [videorecording (DVD)] - Marshall, Kris, 1974-; Jobert, Joséphine; John-Jules, Danny (BBC, 2017)
DI Humphrey Goodman continues to lead his team in investigating criminal activity on the isle of Saint Marie.